Cultural equivalence, reliability and utility of the Portuguese version of the Oral Behaviours Checklist. (26th September 2018) - Barbosa, Cláudia; Manso, Maria Conceição; Reis, Tiago; Soares, Tânia; Gavinha, Sandra; Ohrbach, Richard
Summary: Background: Oral behaviors (OBs) must be assessed as part of a biobehavioural evaluation for patients with temporomandibular disorders (TMD). Objectives: The aims of this study were: to translate and culturally adapt the Oral Behaviors Checklist (OBC) into Portuguese; to evaluate its basic psychometric properties; and to assess the utility of the Portuguese OBC. Methods: The Portuguese translation, cross‐cultural equivalence, and two studies (Pre‐field test, N = 8, and field test, N = 45) of the OBC adhered to official guidelines of the International RDC/TMD Research Consortium (now, INfORM). In the formal test (N = 120) the Portuguese RDC/TMD was used for TMD diagnosis. Results: Translation and cultural equivalence of the OBC into Portuguese was reviewed and approved by an expert panel. In the field test, item agreement between English and Portuguese OBC versions was very good (weighted Kappa ≥ 0.934). Test‐retest reliability of the OBCS umScore was excellent intra‐class correlation coefficient ((ICC) = 0.998, P  <   0.001). As an initial probe into validity using parallel forms, comparison of the sleep bruxism and awake clenching questions included in the RDC/TMD with the corresponding OBC questions yielded excellent (Kappa = 0.932) and very good (k = 0.850), respectively, convergent validity as well as excellent (that is, poor agreement, kappa = 0.013) discriminant validity for these specific OBs. The mean OBCS umScore was significantly lower for the healthy group, compared to the painful TMD group (ANOVA, P  =   0.037). Conclusions: The Portuguese translation of the OBC exhibits cross‐cultural equivalence for use in Portugal, and the instrument performs with acceptable psychometric properties. The validity of the parafunction construct requires additional research in both Portuguese and other languages.